2012
DOI: 10.1007/s00406-012-0312-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of 5-HTT and DAT but not COMT differentially affect verbal and visuospatial working memory functioning

Abstract: Working memory deficits are found in different psychiatric populations and are most pronounced in schizophrenia. There is preliminary evidence from pharmacological studies that the verbal and visuospatial subcomponents of working memory are subject to differential neurotransmitter modulation. Here, we investigated the impact of well-known polymorphisms of the dopamine transporter gene (SLC6A3, DAT) and the catechol-O-methyl-transferase gene (COMT) as well as the serotonin transporter gene (SLC6A4, 5-HTT) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 71 publications
0
26
1
Order By: Relevance
“…Moreover, we went one step further by showing that environmental factors (such as cocaine use) are able to moderate the direction of the polymorphism effects. This finding is especially interesting considering the conflicting results of previous studies suggesting that the effects of the 5-HTTLPR might be task specific (Anderson et al, 2012;Zilles et al, 2012). However, we were able to demonstrate consistent genotype effects across WM tasks measuring spatial (SWM), verbal (LNST), and visuospatial (PAL) WM subdomains (see Table 1 and Supplementary Figure S2).…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Moreover, we went one step further by showing that environmental factors (such as cocaine use) are able to moderate the direction of the polymorphism effects. This finding is especially interesting considering the conflicting results of previous studies suggesting that the effects of the 5-HTTLPR might be task specific (Anderson et al, 2012;Zilles et al, 2012). However, we were able to demonstrate consistent genotype effects across WM tasks measuring spatial (SWM), verbal (LNST), and visuospatial (PAL) WM subdomains (see Table 1 and Supplementary Figure S2).…”
Section: Discussioncontrasting
confidence: 46%
“…However, results of the genetic studies are inconsistent. Some authors found the long allele of 5-HTTLPR to be associated with superior WM performance (Bosia et al, 2010;Zilles et al, 2012), whereas others claimed the short allele to be associated with improved performance (Enge et al, 2011;Anderson et al, 2012). It was argued that these conflicting results may either be due to a task specificity of the 5-HTTLPR (Anderson et al, 2012;Zilles et al, 2012) or due to undetected and moderating environmental factors (Zilles et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to preliminary evidence from pharmacological studies on verbal and visuospatial subcomponents of working memory (WM) being subject to differential neurotransmitter modulation, Zilles et al [4] genotyped 20 healthy controls and 80 patients with schizophrenia, BD, or obsessive-compulsive disorder with respect to the dopaminergic and serotonergic systems. While DAT genotype revealed a significant effect on visuospatial WM, and 5-HTT again a significant one on verbal WM task performance, COMT did not show an influence on either domain.…”
mentioning
confidence: 99%